Wearable measured physical activity profiles and variances in energy expenditure - Hirvonen, Niko-Petteri (2024)
Physical activity is decreasing, and sedentary time is increasing in modern society causing health-, social-, and economic harm at both individual and community levels. The prevalence of diseases directly related to low physical activity is expected to increase significantly, and better means are needed for their prevention.